Estimating the impact of climate change on water levels in a data-poor river basin in southeastern Brazil - Mateus Gonçalves Michelan (IWA Publishing, 2021)
In basins with multiple water uses, it is possible a conflict over water use may occur. This probability increases under a water scarcity scenario. Therefore, it is important to estimate the possible impact of climate change on water availability in this type of basin, to support the decision-making of its users. The Ribeirão do Cipó is an example of a Brazilian watershed susceptible to this situation. Besides having poor hydrological data, it is used for public water supply, electricity generation and recreation. The present work developed a methodology for estimating water availability impacted by climate change, which was particularly applied to this watershed. The methodology consisted of feeding the rainfall–runoff hydrological model called soil moisture accounting procedure with precipitation and evapotranspiration data projected by the Eta-CPTEC regional climate model and nested to three global climate models. The outputs methods were obtained in terms of average monthly flow, for 2010–2039, 2040–2069 and 2070–2099 for the representative concentration pathway (RCP) 4.5 and RCP 8.5 scenarios. Despite the small amount of hydrological data available on the basin, the results were similar to those of the methods used as reference, thus demonstrating that the methodology used can be an alternative in estimating flow for climate change scenarios. HIGHLIGHTS Methodology for estimating flows affected by climate change in a small basin.; Comparison of projected and historical period allows a solid method to estimate flows for basins with lack of data.; Higher CO2 concentration has a direct correlation with maximum flows.; The forecast model results show a methodology consistency.; Long projection did not preclude the flow simulation since the models did not present anomalies.;